Evaluation of the anti-ulcer activities of morus alba extracts in experimentally-induced gastric ulcer in rats - Abdulla, M.A.; Ismail, S.M.; Noor, S.M.; Ahmed, K.A.A.; Ali, Hapipah Mohd (2009)
This study was aimed to elucidate the anti-ulcerogenic effects of Morus alba ethanolic extracts on ethanol induced gastric mucosal injury in animals. Four groups of adult male Sprague Dawley rats were included in the study. 10% Tween 80 was given orally to Group I rats as 2 negative control group. Group 2 and 3 animals received alcoholic extract of Morus alba orally at 250 mg/kg and 500 mg/kg doses, respectively. Omeprazole (20 mg/kg body weight) were given orally to Group 4 rats as a positive control. 60 minutes after their pretreatment, all rats were administered with 5 ml/kg absolute ethanol orally. One hour later, all animals were sacrificed. Grossly, Group I animals showed sever mucosal injury of gastric mucosa. However, a statistically significant reduction of gastric mucosal damage (p<0.05) was seen in animals pretreated with either plant extracts (250 mg/kg or 500 mg/kg body weight) or Omeprazole compared to negative control animals. Rats pretreated with 500mg/kg plant extract or omeprazole have significantly (p<0.05) protected gastric mucosa compared to animals pretreated with 250mg/kg plant extract. Microscopically, animals (Group 1) pretreated with 10% Tween 80 and administered absolute alcohol showed severe gastric mucosal damages, submucosal edema, and leucocytes infiltration. Animals pretreated with plant extracts or omeprazole showed marked reduction of gastric mucosal damage, reduction or edema and leucocytes infiltration of the submucosal layer. These results indicate that M. alba extract exhibits significant anti-ulcerogenic activity in rats.